Colon microbiota fermentation of dietary prebiotics towards short-chain fatty acids and their roles as anti-inflammatory and antitumour agents: A review. (August 2016) - Fernández, Javier; Redondo-Blanco, Saúl; Gutiérrez-del-Río, Ignacio; Miguélez, Elisa M.; Villar, Claudio J.; Lombó, Felipe
Abstract: Some plant polysaccharides cannot be digested by humans, arriving intact to the colon, where they are fermented by a distinct group of anaerobic beneficial bacterial species ( Lactobacillus, Bifidobacterium, Roseburia, Faecalibacterium, Anaerostipes, Coprococcus, etc.). As a result of this fermentation, in the case of some of these compounds, diverse short-chain fatty acids (SCFA) are produced in situ in the colon lumen, mainly acetate, propionate, and butyrate. Acetate and propionate possess principally energetic effects for eukaryotic cells. Butyrate is the preferred energy source for normal colonocytes, contributing to their normal homeostasis, and it is a strong antitumour compound for tumour colonocytes, downregulating cell multiplication pathways and promoting pro-apoptotic routes. These polysaccharides that increase beneficial colon bacteria populations in the colon are called prebiotics. This review will describe their different dietary sources and structures, as well as the metabolic pathways leading to SCFA and the antitumour and anti-inflammatory effect of these SCFA.